User-centric analytic approach to evaluate the performance of sports facilities: A study of swimming pools. (December 2021) - Lau, Erica; Hou, Huiying (Cynthia); Lai, Joseph H.K.; Edwards, David; Chileshe, Nicholas
Abstract: While the performance of sports facilities such as swimming pools is crucial to the health, safety and enjoyment of pool users, little research has been conducted to explore how to analytically evaluate the holistic performance of such facilities from the users' perspective. Even an evaluation framework portraying the key performance attributes of swimming pools is yet to be available. Recognising this research gap, this study aims to adopt a user-centric approach to evaluate the performance of swimming pools and a multi-stage study was initiated. After a thorough literature review, a performance attribute hierarchy for swimming pools was established through a focus group study and then two surveys, covering four swimming pools and 103 pool users interviewed, were conducted in Hong Kong. Analysing the responses using the Analytic Hierarchy Process (AHP) method illustrates that the building services (i.e. utilitarian) aspect of swimming pools is more important than the architectural counterpart, and survey participants cared more about the performance attributes inside water than those outside. This study's novelty lies in that it adopted the user-centric approach, which can differentiate between the relative importance of different swimming pool components and prioritize resources for their maintenance and management. The evaluation framework as well as the findings of the study provides facilities managers with important benchmark criteria for optimising the performance of these sports facilities. In the long run, this study contributes to enabling the project stakeholders to conduct evidence-based decision making over the life cycle of sport facilities development and management. Highlights: A user-centric approach was used to evaluate swimming pool facilities performance. A performance attributes hierarchy was developed for swimming pool facilities. 103 users of four pools were interviewed, whose responses were analyzed using AHP. Importance of building services prevailed over the architectural counterparts. Users cared more about the performance attributes inside water than those outside.